Analisis Strategi Pemeliharaan Untuk Meningkatkan Efektivitas Mesin Ripple Mill Dengan Pendekatan Keefektifan Peralatan - Manullang, Raymond; Lubis, Zulyaden; Raja, Pada Mulia (CV. IRA PUBLISHING, 2025)
This study aims to analyze the operational effectiveness of the Ripple Mill machine using a TPM maintenance strategy approach by measuring OEE. The method used is descriptive quantitative, with primary data from observations and interviews, and secondary data from factory operational documentation. The evaluation was based on three leading OEE indicators: availability, performance, and quality. It was complemented by an analysis of the six significant losses to identify sources of lost production time. The results show that the average OEE value from January to March 2025 reached 96.53%, exceeding the international standard of ≥85%. The most significant losses came from equipment breakdowns (69.75%), followed by minor breakdowns and idling (18.48%). Preventive maintenance programs, operator training, and spare parts availability are recommended. These results demonstrate the effectiveness of the TPM approach in continuously improving machine performance.